THE EFFECT OF PROFITABILITY AND LIQUIDITY TOWARDS THE CAPITAL STRUCTURE ON RETAIL COMPANIES THAT ARE LISTED IN INDONESIA STOCK EXCHANGE IN THE PERIOD OF 2014 – 2015 - Hidayat, Vinny Stephanie; Debbianita, Debbianita (COMPETITIVE, 2020)
The aim of this research is to determine the effect of profitability and liquidity towards the capital structure on retail companies that are listed in Indonesia Stock Exchange. The population of this research is whole of the retail companies that are listed in the Indonesia Stock Exchange in 2014-2015. The method used in this research is explanatory research, and the sampling method used was judgement sampling method. Research hypothesis testing using T test, F test, and multiple regression analysis using SPSS version 20.0. The partially effect is shown by T test, except for profitability variable and the simultaneous effect is shown by F Test. The result of this research shows that the profitability and liquidity affect the capital structure simultaneously. Thus, the hypothesis of the research is empirically supported.Keywords: Capital Structure, Profitability, Liquidity, and Retail Companies